Influence of B2O3 and Basicity on Viscosity and Structure of Medium Titanium Bearing Blast Furnace Slag - Lingtao Bian; Yanhong Gao (Journal of Chemistry)
The effects of B2O3 and basicity (CaO/SiO2) on the viscous behavior and structure of medium titanium bearing blast furnace slag (MTBBFS) were investigated. High temperature viscosimeter was applied to measure the viscosities of CaO-SiO2-MgO-TiO2-Al2O3-B2O3 slag system and X-ray diffraction (XRD), NBO/T ratio, and structure parameter Q were employed to analyze its network structure. The results showed that the viscosity decreased and break point temperature increased with increasing basicity to 1.20. However B2O3 addition gave rise to a decrease in slag viscosity and break point temperature inspite of basicity. The more B2O3 content leads to the more pronounced variation, especially for the slag with larger basicity. The conventional NBO/T formula was revised to predict the structure variation of relatively complicated medium Ti bearing slag based on the work of Yanhong Gao and other researchers. The increase of B2O3 content in slag made parameter Q turn from Q2 to Q1, suggesting that network structure became simpler. It was also noticed that the addition of B2O3 could suppress the formation of perovskite.